STUDI LITERATUR: PEMBANGUNAN INFRASTRUKTUR DAN PEMERATAAN TERHADAP PERTUMBUHAN EKONOMI DAERAH - Yudi Haryadi (JRPA - Journal of Regional Public Administration, 2026)
Infrastructure development is a strategic instrument for promoting regional economic growth, strengthening connectivity, improving productivity, and expanding public access to markets and essential services. However, unequal infrastructure distribution may reinforce regional disparities when its benefits are concentrated in already-developed areas. This study aims to analyze the influence of infrastructure development on regional economic growth, examine the relationship between infrastructure distribution and interregional economic growth, and identify the factors determining the effectiveness of infrastructure in promoting economic equity. The study employed a literature review method with a qualitative descriptive approach. Secondary data were collected from academic books, national and international journal articles, research reports, and relevant official publications. The selected literature was processed through source verification, information reduction, thematic classification, and comparative synthesis. The data were analyzed using descriptive content analysis to identify similarities, differences, patterns, and research gaps in previous studies. The findings indicate that infrastructure generally promotes regional economic growth by improving connectivity, reducing logistics and transaction costs, attracting investment, supporting local businesses, and increasing access to basic services. Nevertheless, its effects vary according to infrastructure type, network integration, regional economic structure, and local capacity. Equitable infrastructure distribution can reduce regional disparities when development priorities are based on service gaps, geographical conditions, local economic potential, and community needs. The study concludes that infrastructure development does not automatically generate inclusive and equitable growth. Its effectiveness depends on integrated planning, accountable governance, sustainable financing, network connectivity, human resource capacity, community participation, proper maintenance, and environmental sustainability. Therefore, physical infrastructure development must be combined with local economic empowerment and human capital development to achieve sustainable and equitable regional growth.